PEMBANGUNAN SISTEM APLIKASI PURCHASE REQUEST PROJECT BERBASIS WEB: STUDI KASUS PADA PT GRAND KARTECT TBK - Muhammad Afifudin (STIKOM CKI, 2016)
In the age of technology that has been developed at this time, amid the rapid development of business throughout the world. Employers must keep up with technology in order to remain competent in business and continue to compete with its competitors in each respective field. Companies can operate like any other company if inside there are the production and operation. Production and operation of an activity creating goods and services that the company offers to consumers. There are obstacles in the course of the project with technological limitations connected computerized network for media booking needs of the project in the